The Correlation Between Vocabulary Mastery and Speaking Skill of Senior High School Students of SMA Angkasa Maros - Dewi Shafira Anindhita; Asriati Asriati; Hasriani G. (State University of Makassar, 2025)
The study aimed to determine the correlation between students’ vocabulary mastery and their speaking skill. The method that the researcher used in this study is quantitative research design with correlational study. This research involved one class in the first-grade students in Class X Science I SMA Angkasa Maros. The sample was taken using the random sampling technique. The findings showed that there was a medium correlation between students’ vocabulary mastery and their speaking skill. It can be verified through the value of the correlation assessment by SPSS 27 is 0.456 and the value of probability of the sig. (2 tailed) is 0.0.25, considered as a significant correlation. Keywords: Correlation, Vocabulary Mastery, Speaking Skill.